Pelatihan Penulisan Artikel Ilmiah bagi Guru di SMP Negeri 2 Banyuasin 1: Upaya Peningkatan Kompetensi Guru - Masagus Firdaus; Tahrun Tahrun; Hanni Yukamana; Sri Wahyu Indrawati; Mulyadi Mulyadi; Santi Mayasari (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
This community service was conducted in response to all teachers’ difficulties in expressing their ideas and publishing them. Based on the preliminary investigation, many teachers had difficulty writing scientific papers. Therefore, this program was conducted. The method used in this program was descriptive qualitative, comprising several stages: distributing preliminary questionnaires, presenting materials, conducting a questions-and-answers (Q&A) session, a personal coaching clinic on writing scientific papers, and distributing final questionnaires to all respondents. The findings from the initial questionnaires showed that most of the teachers or respondents had difficulty understanding the parts and functions of a scientific paper, searching for national and international papers on the SINTA Journal and ScimagoJR websites, and integrating a reference manager (Mendeley). However, after completing the program (community training), which covers presenting material, Q&A, and a personal coaching clinic, most respondents or teachers have shown significant improvement in their scientific paper-writing skills. They have already gained the ability to write a much better scientific paper as a result of the training program.